Defining Corridors for Movement of Multiple Species in a Forest-Plantation Landscape - Vergara-Egert, P (Elsevier B.V., 2020)
Forestry plantations of Pinus radiata, managed through clearcutting method, would offer resistance to the movement of native fauna among remnants of native forest. In this study, we evaluate the possibilities of establishing connectivity corridors for native fauna in a forest landscape dominated by P. radiata, focusing on seven species with some level of specialisation in the use of different land covers and that exhibit different movement strategies. We sampled presences and abundances using several types of sampling to determine the abundance and crossing edge probabilities for the ground-dwelling beetle Ceroglossus chilensis; the mesocarnivores Conepatus chinga, Lycalopex culpaeus and Leopardus guigna; the terrestrial frogs Eupsophus septentrionalis and Pleuroderma thaul, and the understory bird Pteroptochos castaneus. We use species distribution modelling and circuit theory to calculate connectivity for each species. Finally, a spatial priorization approach was applied to obtain two scenarios of least-cost corridors. The results show that species with more specific requirements such as L. guigna, P. castaneus, P. thaul and E. septentrionalis, are unlikely to move through clear cuttings and young plantations, but their movement is possible through adult pine plantations with understory. For species that are habitat generalists such as C. chinga and L. culpaeus plantations were suitable for movement. The management of forest plantations should use multi-taxa assessments in the design of biological corridors that allow the connection of forest fragments. © 2020 The Authors